Decision-making under uncertaintly in remanufacturing processes: An exploratory study - Anjar Priyono (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2015)
Most decisions in remanufacturing focus on a specific sub-system within the production process and neglect how the decision interacts with other decisions. This study aims to investigate decision-making within remanufacturing. The research identifies specific decisions found in remanufacturing processes and analyses their interplays with other decisions. Quite often, one decision will affect other decisions and the result is that the remanufacturing process becomes more complicated. This is not only because there are many uncertainties in remanufacturing, but also because of the effects of interactions. In particular, this research examines how a company deals with uncertainties in decision-making during the remanufacturing processes. A GRAI grid is used to map the positions of various decisions made throughout the remanufacturing process. This is used as it displays the overall remanufacturing process in a graph, so that interplays between decisions can be seen more clearly. The use of GRAI grid to present interplays between the decisions is remanufacturing is the novelty of this study. It is the first time the grid was utilised in the area of decision making remanufacturing context. The methods utilised by remanufacturing companies to overcome the complexities of decision-making are also discussed. Lastly, directions for future research are presented.